Efektivitas Konseling Kelompok dengan Teknik Thought Stopping dalam Mereduksi Body Disasstisfaction pada Mahasiswa - Kalimatussadia, Kalimatussadia; Jannati, Zhila; Muslih, Yuyun Nuriyah; Asriyana, Asriyana (Journal of Society Counseling, 2024)
This research is entitled "Effectiveness of Group Counseling using the Thought Stopping Technique in Reducing Body Disastisfaction in Students". This research is motivated by the phenomenon of body dissatisfaction or dissatisfaction with body shape, so that negative judgments arise in individuals. The aim of this research is to determine the level of body disasstisfaction before and after being given group counseling using the thought stopping technique, and to determine the effectiveness of group counseling using the thought stopping technique in reducing body disasstisfaction in students. The type of research used is quantitative research with experimental methods, while the research design is pre-experimental design with a One-Group Pretest-Posttest Design. Sampling used purposive sampling technique. The T test results show that the significant value (2-tailed) of 0.003 is smaller than 0.05, meaning that Ha is accepted and H0 is rejected, and there is a difference between the pretest and posttest. This research helps to reduce negative thoughts and replace them with more positive thoughts.